2013
DOI: 10.1089/ars.2011.4440
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Variation in the Glutathione-S-Transferase 4 Gene Determines Neurodegeneration After Traumatic Brain Injury

Abstract: Aim: Genetic factors are important for outcome after traumatic brain injury (TBI), although exact knowledge of relevant genes/pathways is still lacking. We here used an unbiased approach to define differentially activated pathways between the inbred DA and PVG rat strains. The results prompted us to study further if a naturally occurring genetic variation in glutathione-S-transferase alpha 4 (Gsta4) affects the outcome after TBI. Results: Survival of neurons after experimental TBI is increased in PVG compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Lastly, a recent study clearly demonstrates that intracerebral injection of HNE results in neurodegeneration. 35 Therefore, HNE can impair key areas in the brain, leading to neuronal cell death. Carnosine, as a carbonyl scavenger and antioxidant, can provide protection against HNE and decrease neurodegenerative disorders, 36 but its action is not limited to HNE-dependent damage.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…Lastly, a recent study clearly demonstrates that intracerebral injection of HNE results in neurodegeneration. 35 Therefore, HNE can impair key areas in the brain, leading to neuronal cell death. Carnosine, as a carbonyl scavenger and antioxidant, can provide protection against HNE and decrease neurodegenerative disorders, 36 but its action is not limited to HNE-dependent damage.…”
Section: Hne and Diseases Associated With Oxidative Damage: Links To mentioning
confidence: 99%
“…In this section we will briefly review detection of lipid peroxidation in clinical TBI. Lipid peroxidation end products such as malondialdehyde, 4-HNE and isoprostanes have been shown to increase in bio-fluids and brain tissue samples from TBI patients (Al Nimer et al, 2013; Cristofori et al, 2001; Cristofori et al, 2005; Kasprzak et al, 2001; Lin et al, 2014b; Lorente et al, 2015; Niki, 2014). Despite criticism for lack of specificity and artefactual production during analytical processing, malondialdehyde (MDA) and thiobarbituric acid reactive substances (TBARS) remain the most commonly used markers of lipid peroxidation in clinical TBI, and their increase in cerebrospinal fluid (CSF) and serum have been associated with severity of injury and mortality (Cristofori et al, 2001; Cristofori et al, 2005; Kasprzak et al, 2001; Lin et al, 2014b; Lorente et al, 2015).…”
Section: Detection Of Lipid Peroxidation In Clinical Tbimentioning
confidence: 99%
“…It forms covalent adducts with proteins and can be detected by immunohistochemistry (Niki, 2014). A recent study reported that 4-HNE-conjugates are present in neurons in human TBI but were not detected in CSF (Al Nimer et al, 2013). …”
Section: Detection Of Lipid Peroxidation In Clinical Tbimentioning
confidence: 99%
“…This strain was used to finely map Vra1 , and several candidate genes were discovered [ 9 ]. A later study determined Glutathione S -transferase alpha 4 ( Gsta4 ) as the strongest candidate gene regulating neurodegeneration in response to VRA [ 10 ] and traumatic brain injury (TBI) in DA.VRA1 congenic rats [ 11 ].…”
Section: Introductionmentioning
confidence: 99%